Length of stay in intensive care unit and characteristics of COVID-19 patients: a single-center observational retrospective study in Hospital Metropolitano, Quito, Ecuador - Farinango, Cecilia; Altamirano, Fabián; Delgado, César; Fors Lopez, Martha (Metro Ciencia, 2022)
Introduction: COVID-19 has been identified by the World Health Organization as a global pandemic. Objectives: The study aims at presenting data on COVID-19 hospitalization cases from march 2020 to January 2021 in Hospital Metropolitano of Quito, Ecuador. Methods: Retrospective study in 515 hospitalization records from adult subjects. Results: We included 332 males and 183 females, 91 patients were admitted to the intensive care unit (ICU) and the mean (±SD) length of ICU stay was 13.5 ± 8.2 days and mean (±SD) length of hospital stay was 5.9 (±3.3) days. It was observed 7.2% of deaths. Thirty-four percent of the patient admitted in ICU died and had a higher mean age compared to survivors (65.6 ± 13.4 vs 56.3 ± 16.1, P = 0.000). The most prevalent comorbidities were hypertension, hypothyroidism and diabetes. There were significant differences in the neutrophil counts, D-dimer levels, creatinine, glucose, IL6, triglycerides (TGL), lactate dehydrogenase (LDH), troponin, sodium and potassium count between survivors and non survivors. The most frequent symptoms were dyspnea, fever and cough. Conclusions: Patients admitted to the intensive care unit had longer length of stay, were older and with lower oxygen saturation level. The laboratory parameters were significantly higher in patients who died. Abnormal count of neutrophils and LDH as well as age were risk factors for mortality in these patients.